Increasing the Reliability of Dust Collector Machine IDC001 Using Preventive Maintenance with Continuous Monitoring Activity in Automotive Company - Anastasia Lidya Maukar; Pandu Adi Cakranegara; Tantyo Edo Wicaksana (President University, 2020)
As one of the main vital for automotive company, the maintenance of machine is very vital to be maintained and controlled to prevent any meaningless downtime. But during January 2015 until November 2018, machine is the highest downtime contributor for molding line with total downtime 2320.49 hours. Especially for dust collector machine IDC001 that contribute the highest downtime of the machines. It is caused by the current preventive maintenance schedule still not considering the machine reliability. The schedule also cannot represent the actual lifetime of its critical components which are dust tube, shaft, v-belt, and bearing. Moreover, there is no any data recorded about the components performance that make the maintenance team cannot predict the component lifetime accurately. The objectives of this research are to achieve 80% reliability and to get more data of component performance by proposing the new preventive maintenance schedule and continuous monitoring activity. After several failure functions calculation, then the new preventive maintenance schedule is established. Through the analysis of what the current maintenance system needs today, there are vibration monitoring and dust concentration monitoring activities that will be proposed to get more data to predict the component lifetime in the future. By implementing the proposed preventive maintenance schedule and continuous monitoring activities, the maintenance team able to get more data to predict the component lifetime and the reliability of each component will increase into 80% with total savings IDR 830,645,805.